424 Child Bicyclists' Perceptions of Safety: Applying Haddon's Matrix to a Qualitative Study. (20th November 2022) - Aucoin, Janet; Aryal, Sarina; McCormack, Gavin; Nettel-Aguirre, Alberto; Winters, Meghan; Hagel, Brent
Abstract : Background: Bicycling can be a beneficial physical activity for children; however, child and parent perceptions of bicyclist safety may influence participation. The Haddon's Matrix breaks down the factors (human, vehicle, environment) and phases (pre-injury, injury, post-injury) that relate to injury outcomes. It has been widely used in quantitative studies of road safety, but less so in qualitative work. Applying Haddon's Matrix to injured child bicyclist interview data may offer insights across qualitative and quantitative paradigms. Aim: To explore injured child bicyclists' perceptions of safety using the Haddon's Matrix. Methods: Injured child bicyclists (aged 5–17) who presented to participating children's hospitals in Vancouver, Calgary, or Toronto from May 2021 - October 2021 were recruited. Forty participants provided responses to open-ended questions on bicycling safety in an interview. A qualitative framework analysis approach was used to identify themes according to the factors and phases of the matrix. Results: Of the factors children perceived as influencing safety, the majority were in the pre-injury phase, with fewer factors in the injury and post-injury phases. Within the pre-injury phase, over half of the factors mentioned related to the physical environment such as surface quality, gravel, and bicycling infrastructure. Children consistently perceived interactions with motor vehicles and a lack of separation from them as reasons for feeling unsafe while bicycling. Conclusion: Children can express factors that influence their perceptions of safety and that align with the Haddon's Matrix. It is important to integrate children's voices to better understand their perceptions of bicycling safety.